2017
DOI: 10.18805/ag.d-4664
|View full text |Cite
|
Sign up to set email alerts
|

Performance of rice varieties with types of seedling under late planted lowland situation

Abstract: A field experiment was conducted under late planted lowland situations during wet seasons of 2012 and 2013 at Jorhat to evaluate the performance of 3 late planted sali (kharif) rice varieties (Prafulla, Gitesh and Monoharsali) under 3 planting dates (10, 20 and 30 September) with 2 types of seedling (Nursery seedling and double planted seedling). Results revealed that delaying planting dates from 10 September to 30 September significantly and consistently reduced both grain and straw yields along with all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Similar was the trend in net returns and benefit-cost ratio. Reduction in yield due to delay in planting was also reported by Changmai and Thakuria (2017), Singh and Thakur (1991), Thakur et al (1996) and Thakuria et al (2017).…”
Section: Varietysupporting
confidence: 65%
“…Similar was the trend in net returns and benefit-cost ratio. Reduction in yield due to delay in planting was also reported by Changmai and Thakuria (2017), Singh and Thakur (1991), Thakur et al (1996) and Thakuria et al (2017).…”
Section: Varietysupporting
confidence: 65%
“…In Assam, primary, secondary nurseries and main field were locally known as Bechan bari, Bolon bari and Dhan bari, respectively [14]. As compared to direct transplanting to main field, a greater number of seedlings (generally, 6-12/hill) are maintained at less spacing of 8-12 cm × 8-12 cm covering 65-70 hills/m 2 land area in secondary nursery [2,21]. In each nursery, nutrient, water managements and plant protection strategies were ensured properly to nurture the seedlings well.…”
Section: The Description Of the Process Of Double Transplantingmentioning
confidence: 99%
“…They noticed early maturity (10 days earlier) of crop, less weed, pest and disease infestations, greater yield, high labour cost, less seed and pesticide costs and profitability under DT method as Naicha method. Earlier, an attempt to standardise the date of transplanting, spacing and seedlings/hill in DT method was made by Thakuria et al [2], in which maximum growth and yield attributes were observed under transplanting of 3 seedlings/hill on 10th September at spacing of 20 cm × 10 cm (Table 6). As a consequence, grain yield, straw yield, harvest index, net return and B:C were found highest under the same in DT method (Table 6).…”
Section: Role Of Double Transplanting As a Contingency Approachmentioning
confidence: 99%
See 1 more Smart Citation